P026 Control of Α2, 6-sialylation in B-cells, and consequences of reduced B-cell sialylation in patients with rheumatoid arthritis. (March 2019) - Johnston, L; Ouboussad, L; Aslam, A; Buch, MH
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Sialic acids are a family of 9-carbon sugars, added to the termini of glycoprotein chains, which are present on the surface of many cells, and secreted proteins. 1 Sialic acids on glycan chains of the Fc fragment of IgG molecules can affect how IgG binds Fc receptors. 2 In RA and other autoimmune conditions, disease specific auto-antibodies display decreased Fc sialylation compared with normal IgG. 3 It has also been shown that plasmablasts from patients with RA display reduced cell surface sialylation compared to healthy control cells. 4 Factors which determine B-cell surface sialylation, including regulation of ST6Gal1and NEU1 which add and cleave sialic acid from glycoprotein chains respectively, and consequences of altered sialylation have not been well described. Objectives: The aim of this study was to investigate factors which influence α2, 6-sialylation in B-cells from the peripheral blood of healthy controls and patients with RA, and to investigate regulation of expression of ST6Gal1 and NEU1 in B-cells. Methods: B-cells isolated from the peripheral blood of healthy volunteers were cultured for 48 hours in the presence of TLR ligands, anti-IgM, CD40L, cytokines (TNF, IL-4, IL-6, IL-17) before α2, 6-sialylation of the B-cell surface, and mRNA expression of genes related to α2, 6-sialylation were measured by SNA lectin flow cytometry, and qPCR respectively. PBMCs were also isolated from peripheral blood and T and B-cells activated using CD3/28 beads and anti-IgM/CD40L respectively, before measuring B-cell sialylation and expression of ST6Gal1 and NEU1 mRNA. Results: Surface α2, 6 sialylation was found to be increased in B-cells stimulated with TLR ligands or anti-IgM/CD40L. This was accompanied by a decrease in expression of both ST6Gal1 and NEU1 mRNA over 48 hours. Surface sialylation was also increased by activated T-cells in co-culture experiments, however sialylation was reduced in B-cell cultures in the presence of TNF. Conclusions: α2, 6-sialic acid is upregulated on the surface of healthy control B-cells in response to activation in vitro, and may be downregulated by TNF. Further experiments will determine if the environment in which naïve/memory B-cells are activated determines plasmablast/plasma cell sialylation, and if B-cells from patients with RA undergo the same changes in response to stimuli. References: Traving C, Schauer R. Cell Mol Life Sci 1998;54:1330–1349. Sondermann P, et al. PNAS 2013;110:9868–9872. Dekkers G, et al. Front Immunol 2018;9:553. Pfeifle R, et al. Nat Immunol 2017;18(1):104–113. Disclosure of Interest: None declared.